E-Commerce Business Analysis: Challenges and Strategies to Improve Business Performance - Muhammad Irhan Arya Fathasyah; Rika Lidyah (Takaza Innovatix Labs Ltd., 2024)
The development of information technology is driving the growth of e-commerce as a vital part of the digital economy, offering opportunities for market expansion and increased business efficiency. However, e-commerce businesses also face various challenges that impact their performance and sustainability. This study aims to analyze the main challenges of e-commerce and strategies that can be implemented to improve business performance. The study uses a conceptual approach with qualitative methods through a literature review of national and international scientific literature. The results of the study indicate that the main challenges of e-commerce include high market competition, changes in consumer behavior, limited human resources, and technological and data security issues. Therefore, adaptive strategies such as digital marketing, improving service quality, product innovation, and optimal utilization of information technology are needed.